2017
DOI: 10.1080/19440049.2017.1411619
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes of six intense sweeteners by Irish adults

Abstract: This research investigated the intakes of six intense sweeteners: acesulfame-K (E950), aspartame (E951), cyclamate (E952), saccharin (E954), sucralose (E955), and steviol glycosides (E960) in the diets of Irish adults, using data from the National Adult Nutrition Survey. A food label survey that included products currently available on the Irish market supplemented the analysis. Sweetener intakes were investigated using three different exposure scenarios; beginning with a crude assessment which assumed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
4
35
1
Order By: Relevance
“…A total of 19 European studies were identified from peer reviewed journals [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76].…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 4 more Smart Citations
“…A total of 19 European studies were identified from peer reviewed journals [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. A further seven studies were identified from authoritative sources [70,71,72,73,74,75,76].…”
Section: Methodology and Trends In Intakementioning
confidence: 99%
“…Amongst the studies conducted using the Tier 2/Tier 3 approach [58,60,63,64,65,66,67,69], the assessments utilized the full range of consumption values from individuals in the sample population, combined with a single value for the MPL (Tier 2) or actual usage levels (Tier 3), considering a single value (simple distribution) [58,63,69], or the full range of use levels (probabilistic) [60,64,65,66,67]. …”
Section: Methodology and Trends In Intakementioning
confidence: 99%
See 3 more Smart Citations